Mental health problems and hypertension in the elderly: Review from the HOPE Asia Network - Turana, Yuda; Tengkawan, Jeslyn; Chia, Yook C.; Shin, Jinho; Chen, Chen‐Huan; Park, Sungha; Tsoi, Kelvin; Buranakitjaroen, Peera; Soenarta, Arieska A.; Siddique, Saulat; Cheng, Hao‐Min; Tay, Jam C.; et al. (The journal of clinical hypertension (Greenwich, Conn.), 2021)
The “triple burden” of aging population, hypertension, and mental health problems making elderly in Asia is more vulnerable. There is evidence of a bidirectional relationship between mental health and hypertension, which results in lower quality of life, lower rate of treatment adherence, and higher mortality among elderly individuals. It is essential to overcome known barriers and care for the elderly with high‐risk factors in order to address these burdens. This review revealed that elderly with hypertension were more likely to suffer from depression and anxiety. Therefore, debunking myths, creating awareness regarding mental health, and increasing access to mental health resources through holistic community‐based programs would greatly reduce such problems and optimize the chances of success in controlling hypertension‐related problems.